2009
DOI: 10.1177/1010539509348241
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Results of a Community-Based Program on Promoting Healthy Lifestyle for Prevention and Control of Chronic Diseases in a Developing Country Setting

Abstract: The objective of the study is to investigate the effect of a comprehensive community trial on behavioral modification after 2 years of intervention. The interventions of this 6-year, comprehensive community-based study target the whole population, of nearly 2 180 000, living in 2 cities in Iran and are compared with another Iranian city considered as reference. Educational, environmental, and legislative interventions are being conducted at the population level. From the baseline to the second year of evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Of these, most used the term dose when interpreting their results but did not refer to the measurement or operationalisation of dose within their methods or findings. For example, Kelishadi and colleagues [57] state that ‘the overall lower increase of junk food consumption … showed that the dose or intensity of our community-based and school-based interventions, although not sufficient, was necessary to act against other forces in the community’ [57] but did not refer to the measurement of dose elsewhere within the main body of the paper. The effect was that it was not clear what was actually considered the dose of the intervention (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, most used the term dose when interpreting their results but did not refer to the measurement or operationalisation of dose within their methods or findings. For example, Kelishadi and colleagues [57] state that ‘the overall lower increase of junk food consumption … showed that the dose or intensity of our community-based and school-based interventions, although not sufficient, was necessary to act against other forces in the community’ [57] but did not refer to the measurement of dose elsewhere within the main body of the paper. The effect was that it was not clear what was actually considered the dose of the intervention (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Regular physical activity is an important protective factor against several diseases, such as obesity, hypertension, type II diabetes318 and MS 19. In a cross-sectional school-based study on 417 adolescents (243 girls) aged 15-18 years from the Azorean Islands, Portugal, daily step counts and physical activity levels were negatively associated with having one or more metabolic risk factors 22.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected using validated questionnaires 61516181920. Physical activity was assessed by Baecke questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Of these healthy lifestyle behaviors, getting regular leisure time physical activity (LTPA), a healthy diet (DIET), and not smoking (NSMK) have been suggested as 3 major HLHs that play important roles in the primary prevention of cancer, cardiovascular disease, stroke, and diabetes. 8-11 It has also been reported that these 3 HLHs can influence health outcomes among individuals with diabetes either directly by affecting diabetes control or indirectly through their effects on comorbidities and psychosocial factors. 12 One previous study of a nationally representative sample of US adults with diabetes 18 years and older further demonstrated that accumulation of these 3 HLHs is significantly associated with better health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%